Penerapan Good Manufacturing Practice (GMP) dan Sanitation Standard Operating Procedure (SSOP) pada Pengolahan Produk UMKM Rendang - Pria Arjuna; Ngatirah; Sri Hastuti; Ida Bagus Banyuro Parta (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2023)
This study aims to evaluated the application of Good Manufacturing Practice (GMP) and Sanitation Standard Operating Procedure (SSOP) in SMEs processing rendang in Payakumbuh, West Sumatera. This study used a qualitative descriptive method with non-probability sampling technique and used the ISO 9001:2000 Gap Analysis Tools. The results of this study indicated that the application of Good Manufacturing Practice (GMP) to SMEs MK is 80.33. Meanwhile, MN SMEs have a percentage of 79.17. Thus, the two SMEs have met the standard requirements based on to the Rule of the Minister of Industry No. 75 of 2010 and on the application of the Sanitation Standard Operating Procedure (SSOP) to MK SMEs has a percentage of 72.16. Meanwhile, MN SMEs have a percentage of 77.04. Thus MK SMEs must improve to meet the standard requirements based on to the Rule of the Minister of Industry No.75 of 2010 and SMEs of MN have met the standard qualification according to the Rule of the Minister of Industry No.75 of 2010.